PERD 079 Project - Task 4 - Review of work plan and selection of wall assemblies - Rousseau, M. Z.; Cornick, S. M.; Said, M. N.; Maref, W.; Manning, M. M. (National Research Council of Canada, 2008)
This report provides an update on completed tasks as well as activities ahead in the Project entitled Engineered Building Envelope to Accommodate High Performance Insulation with Outdoor/indoor Climate extremes. It also reports on the selection of promising wall assemblies for investigation of their hygrothermal, energy and environmental performance, with the project partners. Canada Mortgage and Housing Corporation and Natural Resources Canada are partners with NRC-IRC in this project. Five innovative wall systems have been selected for assessment, and will be compared to a conventional type of wall construction. The composition of the wall assemblies is described in the report. Ce rapport fournit une mise-à-jour concernant les travaux complétés et les activités à venir dans le projet intitulé Enveloppes du bâtiment mises au point pour recevoir de l'isolation thermique haute performance et exposées à des climats intérieurs et extérieurs extrêmes. Le rapport décrit la sélection d'ensembles muraux prometteurs qui seront examinés en fonction de leur performance énergétique, hygrothermique et environnementale. Cette sélection s'est faite de concert avec les partenaires de l'IRC-CNRC dans ce projet, soit la Société canadienne d'hypothèques et de logement et Ressources naturelles Canada. Cinq ensembles muraux novateurs ont été sélectionnés pour fins d'évaluation comparative avec un ensemble mural conventionnel. La composition des ensembles muraux est décrite dans le rapport. Peer reviewed: No NRC publication: Yes